Mobile Phone Usage Behaviour while Driving among Educated Young Adults in the Urban University - Hazali, Norazlanshah; Masuri, Mohamad Ghazali; Md. Isa, Khairil Anuar (Elsevier, 2012)
Introduction; Students who drive and using mobile phones become a common sight these days. Futile to coordinate shall contribute to road traffic accidents. Objective; This study aims to describe the mobile phone usage behaviour while driving among educated young adults. Methods; A cross sectional study was conducted among student in Klang Valley and their participation was on voluntary basis. Results & conclusion; 66.6% of the participants used a mobile phone while driving where male drivers more often to use it on urban road. Results from this study can inform policy maker to design specific campaigns to minimise this unsafe behaviour.